Yellow pumpkin processing desimination as an alternative food product that of high nutritional value in bendo village - Dewi Marfuah; Tuti Rahmawati; Retno Dewi Noviyanti (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Large tracts of land in the village of Bendo, by the local community the most widely used for agriculture. Although most extensive agricultural land and agricultural lots, the poverty rate in Bendo village is still relatively high even as many as 846 people (37%). It is probably because the majority of low-educated population Bendo village. Low education effect on knowledge and skills of the population in the processing of agricultural products. This is evidenced by the farmers in the village of Bendo is still lacking in the use of agricultural products. The purpose of this program is devoted IbM pumpkin farmer empowerment and mothers do not work in Bendo village which is expected to improve people's lives. The method of implementation: 1) training and direct practice of processing pumpkin into a various foods of high nutritional value, 2) provisioning marketing strategies and product promotion pumpkin, 3) the provision of equipment and supplies, 4) assistance manufacture of processed pumpkin 5) training harvesting and storage of pumpkin, 6) assistance pumpkin harvesting and storage. Achievement of the results of this activity: 1) the participant mothers households acquire the knowledge, understanding and skills in the processing and packaging pumpkin into various foods as an alternative food, 2) mothers who did not work the first did not work may have activity to process pumpkin into a variety of foods that have a higher resale value so that it can help the family economy, 3) the provision of equipment, 4) understanding of strategic marketing and promotion through social media, 5) an increase in the price of pumpkins.